Organisational interventions for preventing and minimising aggression directed towards healthcare workers by patients and patient advocates - Spelten, Evelien; Thomas, Brodie; O'Meara, Peter F; Maguire, Brian J; FitzGerald, Deirdre; Begg, Stephen J (Cochrane database of systematic reviews, 2020)
Workplace aggression is becoming increasingly prevalent in health care, with serious consequences for both individuals and organisations. Research and development of organisational interventions to prevent and minimise workplace aggression has also increased. However, it is not known if interventions prevent or reduce occupational violence directed towards healthcare workers. To assess the effectiveness of organisational interventions that aim to prevent and minimise workplace aggression directed towards healthcare workers by patients and patient advocates. We searched the following electronic databases from inception to 25 May 2019: Cochrane Central Register of Controlled Trials (CENTRAL) (Wiley Online Library); MEDLINE (PubMed); CINAHL (EBSCO); Embase (embase.com); PsycINFO (ProQuest); NIOSHTIC (OSH-UPDATE); NIOSHTIC-2 (OSH-UPDATE); HSELINE (OSH-UPDATE); and CISDOC (OSH-UPDATE). We also searched the ClinicalTrials.gov (www.ClinicalTrials.gov) and the World Health Organization (WHO) trials portals (www.who.int/ictrp/en). We included randomised controlled trials (RCTs) or controlled before-and-after studies (CBAs) of any organisational intervention to prevent and minimise verbal or physical aggression directed towards healthcare workers and their peers in their workplace by patients or their advocates. The primary outcome measure was episodes of aggression resulting in no harm, psychological, or physical harm. We used standard Cochrane methods for data collection and analysis. This included independent data extraction and 'Risk of bias' assessment by at least two review authors per included study. We used the Haddon Matrix to categorise interventions aimed at the victim, the vector or the environment of the aggression and whether the intervention was applied before, during or after the event of aggression. We used the random-effects model for the meta-analysis and GRADE to assess the quality of the evidence. We included seven studies. Four studies were conducted in nursing home settings, two studies were conducted in psychiatric wards and one study was conducted in an emergency department. Interventions in two studies focused on prevention of aggression by the vector in the pre-event phase, being 398 nursing home residents and 597 psychiatric patients. The humour therapy in one study in a nursing home setting did not have clear evidence of a reduction of overall aggression (mean difference (MD) 0.17, 95% confidence interval (CI) 0.00 to 0.34; very low-quality evidence). A short-term risk assessment in the other study showed a decreased incidence of aggression (risk ratio (RR) 0.36, 95% CI 0.16 to 0.78; very low-quality evidence) compared to practice as usual. Two studies compared interventions to minimise aggression by the vector in the event phase to practice as usual. In both studies the event was aggression during bathing of nursing home patients. In one study, involving 18 residents, music was played during the bathing period and in the other study, involving 69 residents, either a personalised shower or a towel bath was used. The studies provided low-quality evidence that the interventions may result in a medium-sized reduction of overall aggression (standardised mean difference (SMD -0.49, 95% CI -0.93 to -0.05; 2 studies), and physical aggression (SMD -0.85, 95% CI -1.46 to -0.24; 1 study; very low-quality evidence), but not in verbal aggression (SMD -0.31, 95% CI; -0.89 to 0.27; 1 study; very low-quality evidence). One intervention focused on the vector, the pre-event phase and the event phase. The study compared a two-year culture change programme in a nursing home to practice as usual and involved 101 residents. This study provided very low-quality evidence that the intervention may result in a medium-sized reduction of physical aggression (MD 0.51, 95% CI 0.11 to 0.91), but there was no clear evidence that it reduced verbal aggression (MD 0.76, 95% CI -0.02 to 1.54). Two studies evaluated a multicomponent intervention that focused on the vector (psychiatry patients and emergency department patients), the victim (nursing staff), and the environment during the pre-event and the event phase. The studies included 564 psychiatric staff and 209 emergency department staff. Both studies involved a comprehensive package of actions aimed at preventing violence, managing violence and environmental changes. There was no clear evidence that the psychiatry intervention may result in a reduction of overall aggression (odds ratio (OR) 0.85, 95% CI 0.63 to 1.15; low-quality evidence), compared to the control condition. The emergency department study did not result in a reduction of aggression (MD = 0) but provided insufficient data to test this. We found very low to low-quality evidence that interventions focused on the vector during the pre-event phase, the event phase or both, may result in a reduction of overall aggression, compared to practice as usual, and we found inconsistent low-quality evidence for multi-component interventions. None of the interventions included the post-event stage. To improve the evidence base, we need more RCT studies, that include the workers as participants and that collect information on the impact of violence on the worker in a range of healthcare settings, but especially in emergency care settings. Consensus on standardised outcomes is urgently needed.